THE RELATIONSHIP BETWEEN CORPORATE VOLUNTEERING AND CORPORATE SOCIAL RESPONSIBILITY: RESULTS OF AN EMPIRICAL STUDY (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
Corporate Volunteering (CV) is a phenomenon that emerged in the second half of the 20th century and began to grow and globalize at the beginning of the 21st century. There seems to be a consensus that the recent growth of Corporate Volunteering is related to the development and growing legitimacy of the concept of Corporate Social Responsibility (CSR). Nevertheless, the theoretical discussion on how the two concepts (Corporate Volunteering and Corporate Social Responsibility) are related is just beginning, while empirical research on how this relationship operates in corporate practice is still incipient. This paper presents preliminary results of a research on this subject carried out in Uruguay in 2016. This is a statistical study that analyses the relationship between the application of corporate volunteering activities and the incorporation of a CSR approach to the management of companies. The incorporation of both types of practices is measured by a self-assessment questionnaire that includes 81 indicators (using a Likert scale to assess them), which were designed based on ISO 26000 Guidance of Social Responsibility[i]. The questionnaire was administered to 96 companies, using a comparative analysis between those that practice Corporate Volunteering and those which do not. The results obtained allow us to support the hypothesis that the application of Corporate Volunteering is positively associated with the incorporation of CSR when managing the relationship between the company and its employees and also with the community. Moreover, these results contribute to a better understanding on how both concepts are related.Keywords: Corporate Volunteering, Employee Volunteering, Corporate Social Responsibility, ISO 26000[i] ISO (2011). Guía de Responsabilidad Social (ISO 26.0000: 2012, IDT). Montevideo: UNIT